AKT Hyperactivation and the Potential of AKT-Targeted Therapy in Diffuse Large B-Cell Lymphoma - Wang, Jinfen; Xu-Monette, Zijun Y.; Jabbar, Kausar J.; Shen, Qi; Manyam, Ganiraju C.; Tzankov, Alexandar; Visco, Carlo; Wang, Jing; Montes-Moreno, Santiago; Dybkær, Karen; Tam, Wayne; Bhagat, Govind; et al. (The American journal of pathology, 2017)
AKT signaling is important for proliferation and survival of tumor cells. The clinical significance of AKT activation in diffuse large B-cell lymphoma (DLBCL) is not well analyzed. Here, we assessed expression of phosphorylated AKT (p-AKT) in 522 DLBCL patients. We found that high levels of p-AKT nuclear expression, observed in 24.3% of the study cohort, were associated with significantly worse progression-free survival and Myc and Bcl-2 overexpression. However, multivariate analysis indicated that AKT hyperactivation was not an independent factor. miRNA profiling analysis demonstrated that 63 miRNAs directly or indirectly related to the phosphatidylinositol 3-kinase/AKT/mechanistic target of rapamycin pathway were differentially expressed between DLBCLs with high and low p-AKT nuclear expression. We further targeted AKT signaling using a highly selective AKT inhibitor MK-2206 in 26 representative DLBCL cell lines and delineated signaling alterations using a reverse-phase protein array. MK-2206 treatment inhibited lymphoma cell viability, and MK-2206 sensitivity correlated with AKT activation status in DLBCL cells. On MK-2206 treatment, p-AKT levels and downstream targets of AKT signaling were significantly decreased, likely because of the decreased feedback repression; Rictor and phosphatidylinositol 3-kinase expression and other compensatory pathways were also induced. This study demonstrates the clinical and therapeutic implications of AKT hyperactivation in DLBCL and suggests that AKT inhibitors need to be combined with other targeted agents for DLBCL to achieve optimal clinical efficacy.